Pengaruh Norma Terhadap Perilaku Presiden Joko Widodo Dalam Pembuatan Kebijakan Penanganan Pengungsi Di Indonesia (Studi Kasus: Peraturan Presiden No 125 Tahun 2016 Tentang Penanganan Pengungsi Dari Luar Negeri) - Ulfa, Diyana Rosyida; Pramono, Sugiarto (Kajian Hubungan Internasional, 2024)
This research aims to find out the reason why President Joko Widodo issued Presidential Regulation No. 125 of 2022. This study uses a qualitative descriptive method by using secondary data types where the source of research data is obtained through intermediary media or indirectly in the form of books, journals, papers, newspapers. , articles and the internet. The results of this study indicate that the reason President Joko Widodo made Presidential Regulation No. 125 of 2016 regarding the handling of refugees is due to the influence of norms such as international norms, domestic norms, human rights norms and as an alternative to the 1951 Convention and 1967 Protocol not being ratified.